Integrating Green History in History Learning Media to Enhance Student’s Ecological Awareness - Khairunisa Ashriana; Ponco Setiyonugroho; Yusuf Budi Prasetya Santosa (Criksetra: Jurnal Pendidikan Sejarah, 2026)
The global environmental crisis requires the education system to instill ecological awareness in the learning pro cess. In the context of history education, the Green History concept offers a new perspective by emphasizing the reciprocal relationship between humans and nature throughout history. This study aims to describe the Green History concept, its integration into history learning media, and its contribution to developing students’ ecological awareness. The research employs a qualitative descriptive approach through literature review of previous studies related to history and environmental education. The findings reveal that integrating Green History into innovative history learning media, such as digital modules, documentaries, and interactive maps, can enhance students’ ecological awareness by encouraging critical reflection on environmental change through time. It is concluded that Green History has significant potential to make history education more contextual, reflective, and sustainability-oriented. Therefore, history educators are recommended to systematically incorporate Green History perspectives into curriculum design and learning media development. Future research is suggested to empirically examine the effectiveness of Green History-based learning on students’ ecological attitudes and behaviors.